Cultural intelligence and heritage impact on choosing foreign tourist destination - Zdravković, Stefan; Peković, Jelena (Hotel and Tourism Management, 2021)
Due to the process of globalization, travel has become much more affordable, so tourists have the opportunity to visit foreign and even some exotic destinations . Market research helps travel agencies in formulating a marketing strategy, which should attract tourists and ensure their satisfaction, which ultimately enables the service provider to make a profit. The purpose and goal of the research is to determine whether cultural intelligence as a push-factor implying the desire of tourists to learn a foreign language, and get to know other cultures and their value systems and cultural heritage as a pull-factor implying touring buildings, and cultural monuments of other countries, influence the choice of foreign tourist destinations. Furthermore, the research examines whether the influence of these variables from the aspect of a demographic characteristic of age is more pronounced in respondents belong to generation Z compared to the generation X respondents. The sample includes 208 respondents from the Republic of Serbia. After statistical processing of the data, the obtained results show that variables have a statistically significant positive impact on the choice of foreign tourist destinations, and that their impact is more pronounced in generation Z respondents compared to those of generation X, so the research provides useful information to marketers and travel agencies.